"فعّالية استخدام الطريقة الموجهة في تعليم مهارة القراءة في معهد "مفتاح العلوم الشرعية, جاندونج - ساري, روسي كومالا; فبريانتا, ريتا (Asian Journal of Islamic Studies and Da'wah, 2024)
In the thesis, the researcher is looking for teacing the skill of reading. Reading skill is the ability to recognize the contents of something written and understand it by reading it or digesting it by heart, but many of the students did not understand the contents of the reading text. This research is done through the students’ questionnaires when the teacher asks about the text that that they are reading. The purposes of this research are to find out the appropriate method for teacing reading skills at the “Miftahul Ulumi Syar’iyyah, Canduang”. The researcher used exsperimental research, and the same researcher worked at the “Miftahul Ulumi Syar’iyyah, Canduang meaning in chapter eigh 40 people, 220 in the exsperimental class and 20 in the control class. The result of the teaching a reading skill to students after using the directed method is the result. The mean for the post-test in the exsperimental semester is 75.5. the average result for the post-test in the control class is 65,5. The researcher found that the result of the calculation letter 2,001 and the result of the table 2,093. So the result of the calculation letter is smaller that the result of the table letter and the difference between them is 0,092. The researcher reached the conclusion that using the directed method is effective in teacing the reading skill and can improve the result of teaching reading to students in the eighth semester at the “Miftahul Ulumi Syar’iyyah, Canduang”.